COVID-19 and environmental health: A systematic analysis for the global burden of biomedical waste by this epidemic. (December 2022) - Ngoc, Suong-Mai Vu; Nguyen, Mai-Anh; Nguyen, Thanh-Lam; Thi, Hue Vu; Dao, Thi Loi; Bui, Thi Minh Phuong; Hoang, Van Thuan; Chu, Dinh-Toi
Abstract: Since the beginning of this outbreak, much evidence stated that the climb in the amount of biomedical waste harmed human health and had adverse effects on the environment. With the increase of cases of COVID-19 all around the globe, the amount of biomedical waste was also constantly rising. Also, many solutions regarding either reducing or recycling biomedical waste. However, the potential global burden of biomedical waste during this pandemic was not yet been analyzed. Herein, we perform a systematic review of literature on these modalities, including mentioning types of biomedical waste, the effect on health, the environment, and methods of handling biomedical waste during this pandemic. A total of 3551 published papers were identified by two databases. In the end, 15 references were selected for this systematic analysis. Most of the included studies focus on research on the impact of medical waste caused by the COVID-19 pandemic on the environment. The total biomedical waste during the COVID-19 pandemic was approximately 16, 649.48 tons/day. Most publications agreed that the amount of waste has also increased due to the rapidly rising number of COVID-19 patients. In 15 articles, we identified 2 mentioning the COVID-19 biomedical waste on health. 9 out of 15 gave out the context related to the solution of BMW by COVID-19. More studies, including meta-analyses, are recommended to shed more light on the effects of medical waste on environmental health during the COVID-19 pandemic. Graphical abstract: Image 1 Highlights: Since the beginning of COVID-19, the climb in the amount of biomedical waste has harmed human health and the environment. This systematic review includes types, effects, and methods of handling biomedical waste. Medical waste during the COVID-19 pandemic was significantly higher than before the epidemic. Medical waste affects environmental health during the COVID-19 pandemic. Need to improve biomedical waste management policies during the COVID-19 pandemic to ensure human health and the environment.